2014
DOI: 10.1371/journal.ppat.1004003
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Theileria annulata Promote Invasive Cell Motility through Kinase Regulation of the Host Actin Cytoskeleton

Abstract: The intracellular, protozoan Theileria species parasites are the only eukaryotes known to transform another eukaryotic cell. One consequence of this parasite-dependent transformation is the acquisition of motile and invasive properties of parasitized cells in vitro and their metastatic dissemination in the animal, which causes East Coast Fever (T. parva) or Tropical Theileriosis (T. annulata). These motile and invasive properties of infected host cells are enabled by parasite-dependent, poorly understood F-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…Since disturbed morphodynamics and cell migration control are intimately associated with the cancerous phenotype, studies in cancer cell lines soon confirmed the promigratory function of MAP4K4 [3,62]. MAP4K4 implications in migration control in the context of cell transformation was also shown in macrophages infected with the protozoan parasite Theileria annulata, where parasite-induced TNFα secretion by the host cell activates MAP4K4 in an autocrine manner, to drive migration and invasion of the host cell [11]. In an inflammatory context as well, MAP4K4 promotes Kaposi Herpes virus-infected cell migration by controlling the expression of genes responsible for motility and invasiveness such as COX-2, MMP-7 and MMP-13.…”
Section: Cell Migration and Invasionmentioning
confidence: 94%
See 4 more Smart Citations
“…Since disturbed morphodynamics and cell migration control are intimately associated with the cancerous phenotype, studies in cancer cell lines soon confirmed the promigratory function of MAP4K4 [3,62]. MAP4K4 implications in migration control in the context of cell transformation was also shown in macrophages infected with the protozoan parasite Theileria annulata, where parasite-induced TNFα secretion by the host cell activates MAP4K4 in an autocrine manner, to drive migration and invasion of the host cell [11]. In an inflammatory context as well, MAP4K4 promotes Kaposi Herpes virus-infected cell migration by controlling the expression of genes responsible for motility and invasiveness such as COX-2, MMP-7 and MMP-13.…”
Section: Cell Migration and Invasionmentioning
confidence: 94%
“…These processes include insulin sensitivity [8], systemic inflammation [9], pathogen-dependent oncogenic progression [10,11] and vascular inflammation and atherosclerosis [12]. In addition to the TNFα-receptor, growth factors (GF) such as PDGF or EGF activate MAP4K4 through receptor tyrosine kinases (RTKs) [2] and trigger the phosphorylation and activation of the MAP4K4 substrates sodiumproton exchanger [1] (NHE1) [13], ezrin, radixin, moesin (ERM) family proteins [14] and actin-related protein [2] (Arp2) [15].…”
Section: Signaling Through Map4k4mentioning
confidence: 99%
See 3 more Smart Citations